Multiproxy taphonomic analysis in the Los Colorados Formation (Upper Triassic), Ischigualasto-Villa Unión Basin, Argentina: A case study through sauropodomorph remains. (October 2022) - Pérez, Leandro M.; Otero, Alejandro; Alonso Muruaga, Pablo J.; Gaetano, Leandro C.; Leardi, Juan M.; Krapovickas, Verónica; Poiré, Daniel G.
Abstract: We present the first taphonomic analysis on basal sauropodomorph dinosaur remains from the Los Colorados Formation. We analyzed 22 bone samples with X-ray diffractometry, three of these in petrographic sections and one of them in SEM. In this article we recognize the taphonomic processes (biostratinomic and fossil-diagenetic) involved in the genesis of the 'La Esquina Local Fauna'. Regarding fossil diagenesis, it was possible to recognize the different processes that acted on the bone remains. In this sense, we analyzed different types of fracture present in the bones and their relationship with expansion generated by changes in the volume of minerals (for example, carbonates, gypsum and anhydrite). Finally, the importance of more taphonomic studies throughout the Los Colorados Formation is highlighted in order to better understand the vertebrate fossil record it contains. Highlights: Sauropodomorph bones were affected by different taphonomic processes. At least three types of fractures associated with volume changes of minerals. The fractures analyzed in the bones are of fossil-diagenetic origin. The fossil record of vertebrate remains is found in well-developed overbank/floodplain deposits and rarely within fluvial channel facies. Major bone loss can be explained by actual exhumation.